Dual versus conventional cardiac resynchronization: A pilot study - Pradip Kumar Ghoshal; Subhraprakash Pramanik; Tanmoy Kanti Goswami; Mondal, Rajarshi; Biswas, Arunava; Asish Biswas (Asian Journal of Medical Sciences, 2024)
Background: Systolic heart failure treatment now includes cardiac resynchronization therapy (CRT) as a necessary element. CRT has been shown to have advantageous impacts on mortality, hospitalization rates, and quality of life. Approximately 30% of patients fail to respond to traditional CRT implantation. Aims and Objectives: This study aimed to compare the outcome of dual resynchronization by placing the right ventricular pacing lead at His bundle or left bundle branch area against conventional CRT. Materials and Methods: This longitudinal follow-up study of a total of 35 patients undergoing CRT device placement for assessment of safety, efficacy, and feasibility of the procedure and post-procedural complications and correlation with parameters obtained from electrocardiogram and echocardiography parameters in a tertiary care set up in India. Results: Among this matched population (mean age 64 years) there was a higher responder rate with the newer technique of dual resynchronization compared to conventional CRT (83% vs. 70%). Conclusion: Dual resynchronization therapy is feasible and safe and provides better electrical resynchronization compared to conventional CRT and could be a better alternative, especially when suboptimal electrical resynchronization is obtained.